Research on safety supervision data sharing of railway construction projects based on edge computing - Liang YANG; Chunhui PIAO; Yuhong LIU; Meimei JI (Dianxin kexue)
Information security monitoring system is widely used in railway construction projects,but the existing safety supervision model has problems such as high server load,heavy network bandwidth pressure,monitoring data can’t be effectively shared,key monitoring data may be tampered,and security accident responsibility is difficult to determine.A credible sharing model of safety supervision data for railway construction projects based on edge computing was proposed.On one hand,the construction of a safety monitoring edge computing framework for construction projects was constructed,and the data processing flow of edge nodes was described; on the other hand,a trusted data sharing framework based on blockchain was established,and a safety supervision data sharing process was designed and trusted sharing data was implemented through smart contracts.The proposed solution combined with edge computing and blockchain technology,which not only could strengthen the safety supervision of railway construction projects by industry authorities,but also provide new opportunities for stakeholders to share safety monitoring data in real time.